1977
DOI: 10.2307/3428508
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Binding of Chlorinated Ethylenes to Macromolecules

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…No further degradation of chloroform was observed even after incubating for prolonged periods ([96 h), by nonimmobilized cells after the first cycle unlike the immobilized cells. Alvarez-Cohen and McCarty (1991) have speculated that phosgene and trichloroethylene epoxide are responsible for the product toxicities of chloroform and trichloroethylene, since both compounds exhibit irreversible binding to proteins thought to result in toxic behavior in mammalian system (Bolt and Filser 1977;Pohl et al 1977). A similar reaction may have caused the toxicity observed with this Bacillus sp.…”
Section: Comparisons Of Chloroform Degradation By Free and Immobilizementioning
confidence: 89%
“…No further degradation of chloroform was observed even after incubating for prolonged periods ([96 h), by nonimmobilized cells after the first cycle unlike the immobilized cells. Alvarez-Cohen and McCarty (1991) have speculated that phosgene and trichloroethylene epoxide are responsible for the product toxicities of chloroform and trichloroethylene, since both compounds exhibit irreversible binding to proteins thought to result in toxic behavior in mammalian system (Bolt and Filser 1977;Pohl et al 1977). A similar reaction may have caused the toxicity observed with this Bacillus sp.…”
Section: Comparisons Of Chloroform Degradation By Free and Immobilizementioning
confidence: 89%
“…Additionally, the kidneys, spleen, and small intestineare involved in metabolism of TCE because these tissues are sites of cellular protein binding of metabolites from TCE (Bolt and Filser, 1977;Dalbey and Bingham, 1978;Bergman, 1983; Davidson and Beliles, 1991). Cytochrome P-450-mediated metabolism plays an important role in the toxicity of TCE (Ikeda and Ohtsuji, 1972;Bonse and Henschler, 1976;Henschler et al, 1979;Guengerich, 1982, 1983;Dekant et al, 1984;Prout et al, 1985;U.S.…”
mentioning
confidence: 97%
“…Synthetic epoxides of trichloroethylene and tetrachloroethylene have been shown to be genotoxic (Kline et al, 1982) and induce transformation in cultured hamster cells (DiPaolo and Doniger, 1982), but neither was carcinogenic by chronic skin application or subcutaneous injection in mice (Van Duuren et al, 1983). For several other compounds of this type, macromolecular binding, including to DNA, has been demonstrated in vitro (Van Duuren and Banerjee, 1976;Bolt and Filser, 1977;Laib et al, 1979;DiRenzo et al, 1982;MacDonald et al, 1982;Stott et al, 1982;Parchman and Magee, 1982;Miller and Guengerich, 1983). However, DNA binding of chlorinated ethanes and ethylenes other than monochloroethylene and l, !-dichloroethylene has been nonexistent or of a very low order (Schumann et al, 1980;Stott et al, 1982), and specific adducts have not been identified (Parchmann and Magee, 1982;Stott et al, 1982).…”
Section: Discussionmentioning
confidence: 99%